2018
DOI: 10.1155/2018/9462475
|View full text |Cite
|
Sign up to set email alerts
|

A Seven-Year Retrospective Study on the Surveillance of Hepatitis B in Laos

Abstract: Objective Lao PDR is one of the most highly endemic countries for hepatitis B in Asia and the second country for liver cancer incidence. Therefore, the follow-up of infected individuals through predictive serological markers is of utmost importance to monitor the progression of the pathology and take the decision on treatment. Methods A retrospective-descriptive cohort study was conducted on 3,857 HBV-infected patients. Information about infection status (viral load, VL), liver function (aminotransferases), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…All patients presenting at CILM were diagnosed anti-HCV(?) using rapid point-of-care tests with questionable efficacy according to our experience (Paboriboune et al 2018). This diagnosis was established during routine health check-ups or specialized gastroenterology consultations.…”
Section: Discussionmentioning
confidence: 99%
“…All patients presenting at CILM were diagnosed anti-HCV(?) using rapid point-of-care tests with questionable efficacy according to our experience (Paboriboune et al 2018). This diagnosis was established during routine health check-ups or specialized gastroenterology consultations.…”
Section: Discussionmentioning
confidence: 99%
“…Among the patients, 10.6% had both a high level of HBV DNA over 10,000 IU/mL and elevated aminotransferases. However, only 2.4% of them received treatment for chronic hepatitis [10,11].…”
Section: Hepatitis B Virusmentioning
confidence: 99%
“…More recently, a retrospective study conducted on 1765 HCV-infected patients showed that, in Vientiane, 28% had high viral loads (>6log10). About 23% of patients had levels of aminotransferases indicative of liver damage >40 IU/mL, but less than 20% of them received antiviral drugs [10,11]. In Laos, circulating strains overwhelmingly belong to genotype 6 >95%, the Southeast Asian version of HCV, with frequent viral isolates specific to the local population [18][19][20].…”
Section: Hepatitis C Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…The recommended upper limit of normal (ULN) for ALT for guiding the management of chronic HBV infection is >ULN, where ULN is defined by local laboratory . Elevated liver enzymes have been reported in HBV‐infected individuals in several Asian studies . Elevated ALT levels have been positively correlated with HBV DNA positivity, liver stiffness and an increased risk of fibrosis, cirrhosis and HCC in Asian patients with chronic HBV infection .…”
Section: Pre‐treatment Assessments In Individuals With Chronic Hbv Inmentioning
confidence: 99%